2021
DOI: 10.1111/are.15430
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fish meal replacement with toasted guar meal on growth, food conversion, digestive enzyme activity and final carcass composition of rohu,Labeo rohita

Abstract: A growth trial was conducted for 60 days in 4 × 4 m outdoor cement tanks with soil base to evaluate growth, feed conversion efficiency, carcass composition and digestive enzyme activity of rohu, Labeo rohita, fed diets incorporated with guar meal replacing fish meal. The isonitrogenous and isocaloric diets used were—a fish meal based diet (Control) and diets with fish meal replaced at 30%, 60% and 90% levels with guar meal. The growth parameters, feed conversion and protein efficiency ratio, survival and condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In general, the activities of enzymes tested in H. pulchellus were lower in hepatopancreas compared to that in intestine. This phenomenon is in agreement with the findings by Umalatha et al (2016) and Barlaya, Ananda Kumar, et al (2021) in Labeo rohita.…”
Section: Ta B L Esupporting
confidence: 94%
See 1 more Smart Citation
“…In general, the activities of enzymes tested in H. pulchellus were lower in hepatopancreas compared to that in intestine. This phenomenon is in agreement with the findings by Umalatha et al (2016) and Barlaya, Ananda Kumar, et al (2021) in Labeo rohita.…”
Section: Ta B L Esupporting
confidence: 94%
“…The crude enzyme extracts of intestine and hepatopancreas from test animals were prepared as explained by Barlaya, Ananda Kumar, et al (2021) and stored at − 20°C. All extraction procedures were carried out at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is not clear if such increases result from the higher secretion of the pancreatic enzymes to the lumen and/or they are derived from the microbes of the lumen. Barlaya et al [41] have shown that increase in a plant protein source in fish diet decreases the activity of digestive enzymes in the intestine, but not hepatopancreas. Moreover, organic acids may have no significant effects on digestive enzymes in the pancreas, as evidenced in shrimp [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the growth performance and feed utilization, the digestive enzymes activity was also an important index for determining the potential of available protein sources as dietary FM substitutes for aquatic animals [ 26 ]. The AMS, LPS, and trypsin, three major digestive enzymes, are essential for the initial degradation of dietary starch, lipid, and protein, respectively [ 26 ]. The higher digestive enzymes activity represents the stronger digestive capacity.…”
Section: Discussionmentioning
confidence: 99%